Pelatihan interpretasi dalam pengembangan agrowisata di Desa Sidan Kabupaten Gianyar Bali - Hubner, Ira B; Juliana, Juliana; Lemy, Diena; Pramezwary, Amelda (IKIP SILIWANGI, 2025)
communities. The agrotourism trend is a challenge and an opportunity to increase local community income while preventing land conversion from agriculture to other uses. Interpretation is an inseparable part of shaping the visitor experience at tourist attractions including agrotourism. Visitors who know the tourist destination well will appreciate and support agrotourism development efforts more and will tell others to visit the place. Sidan Village is one of the villages in Gianyar Regency that has developed organic farming and obtained organic certification in 2019. Mentik Susu rice is produced by farming with a subak irrigation system and the use of compost. With its agrotourism attractions, it is very important to increase the understanding of tourist village managers to develop interpretation efforts. For this reason, in this Community Service, interpretation training was carried out, including socialization of the importance of interpretation, benefits, types and manufacturing processes, with 30 participants. The implementation method will be carried out in the form of workshops for tourist village managers, Tourism Awareness Groups, and the local community. The results of this Community Service are increased knowledge of participants about the benefits and types of interpretation, as well as follow-up to the interpretation-making process.